2022
DOI: 10.3390/ijms23063406
|View full text |Cite
|
Sign up to set email alerts
|

Formate Dehydrogenase Improves the Resistance to Formic Acid and Acetic Acid Simultaneously in Saccharomyces cerevisiae

Abstract: Bioethanol from lignocellulosic biomass is a promising and sustainable strategy to meet the energy demand and to be carbon neutral. Nevertheless, the damage of lignocellulose-derived inhibitors to microorganisms is still the main bottleneck. Developing robust strains is critical for lignocellulosic ethanol production. An evolved strain with a stronger tolerance to formate and acetate was obtained after adaptive laboratory evolution (ALE) in the formate. Transcriptional analysis was conducted to reveal the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Adaptive laboratory evolution to improve formate tolerance in S. cerevisiae CEN.PK 113-5D led to a ~ 3,000-fold higher expression of the formate dehydrogenase-encoding genes FDH1 , YPL276W , and FDH2 ( 49 ). Overexpression of FDH1 has been demonstrated to increase tolerance to formic acid and acetic acid, through decomposition of formic acid and generation of additional ATP, respectively ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…Adaptive laboratory evolution to improve formate tolerance in S. cerevisiae CEN.PK 113-5D led to a ~ 3,000-fold higher expression of the formate dehydrogenase-encoding genes FDH1 , YPL276W , and FDH2 ( 49 ). Overexpression of FDH1 has been demonstrated to increase tolerance to formic acid and acetic acid, through decomposition of formic acid and generation of additional ATP, respectively ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the sporulation of YI30 resulted in MSCs with differential ability to withstand increasing concentrations of formic acid and was useful for the selection of a few candidates with promising phenotypes to be further studied to both shed light on the still poorly investigated mechanism of formic acid tolerance in S. cerevisiae and to develop superior yeast strains with increased resistance to this weak acid [ 57 , 58 ]. Few MSCs, indeed, showed a lower lag phase, thus reacting much faster than the parental strains thanks to strong and strain-specific intracellular metabolomic reactions.…”
Section: Resultsmentioning
confidence: 99%
“…This makes ScFDH1 overexpression play a bigger role in the fermentation of lignocellulosic hydrolysates. 24 NADH plays a vital role in CO 2 fixation by FDHs. Desirably, during the production of ethanol, TCA and biomass growth from glucose generate surplus NADH.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Consequently, the co-production of bioethanol and valueadded formate from CO 2 can significantly decrease production costs. In our previous study, 24 ScFDH1 was overexpressed in the main bioethanol producer Saccharomyces cerevisiae. It was reported that overexpressed ScFDH1 improved the tolerance to formic acid and acetic acid simultaneously derived from lignocellulosic hydrolysate by increasing the cell viability.…”
Section: Introductionmentioning
confidence: 99%